The improvement guide : a practical approach to enhancing organizational performance - Moen, Ronald D.; Nolan, Kevin M.; Nolan, Thomas W.; Norman, Clifford L.; Provost, Lloyd P. (Jossey-Bass, 2009)
This new edition of this bestselling guide offers an integrated approach to process improvement that delivers quick and substantial results in quality and productivity in diverse settings. The authors explore their Model for Improvement that worked with international improvement efforts at multinational companies as well as in different industries such as healthcare and public agencies. This edition includes new information that shows how to accelerate improvement by spreading changes across multiple sites. The book presents a practical tool kit of ideas, examples, and applications.